Transcriptomic Study of Gracilaria Changii (Gracilariales, Rhodophyta) By Expressed Sequence Tags and Cdna Microarray Approach - Seddon, Teoh (2009)
Gracilaria is one of the most extensively harvested seaweeds throughout the world due to its economic importance as an agarophyte for global agar production. In this study, Gracilaria changii, an indigenous seaweed species in Malaysia known for its high quality agar was chosen for transcription profiling. A total of 990 expressed sequence tags (ESTs) consisting of 766 tentative unique genes (TUGs) have been generated. These TUGs comprise 643 TUSs (tentative unique singletons) and 123 TUCs (tentative unique contigs). The putative identity of TUGs was identified by using Basic Local Alignment Search Tool X (BLASTX) algorithm and classified according to the functional groups in Kyoto Encyclopedia of Genes and Genomes (KEGG). The result showed that 198 TUGs (25.85%) have significant matches to the annotated proteins and 81 TUGs (10.57%) have significant matches to the unknown proteins in the non-redundant protein database in the GenBank; whereas the remaining 487 (63.58%) TUGs had non-significant matches or no matches to sequence from other organisms. Similar to animals and plants, G. changii showed preference for purine residues at -3 position and guanidine at +4 position at the translational initiation signal. On the other hand, the 3' untranslated region of G. changii was found to have relatively less stringent polyadenylation process compared with plants and animals in producing mature mRNA. A cDNA microarray consisting of approximately 3,000 cDNA probes was constructed and used for the hybridization of cDNAs synthesized from G. changii samples cultured under conditions with and without light to understand the genetic acclimation of G. changii to light deprivation. The results suggested that genes related to photosynthesis, oxidative stress and sulfate metabolism were down-regulated during light deprivation. The cDNA microarray data were further verified by using real-time PCR. The results of the real-time PCR analysis of four genes encoding light-harvesting complex I polypeptide (DV962275.1), low molecular mass early light-inducible protein (DV964113.1), 14-3-3 protein (DV965610.1) and sonic hedgehog protein precursor (DV967367.1) supported the expression patterns demonstrated using cDNA microarray.